Synthesis and organic field effect transistor properties of isoindigo/DPP-based polymers containing a thermolabile group. Issue 27 (14th March 2017) - Shaker, Mohamed; Park, Byoungwook; Lee, Jong-Hoon; kim, Wonbin; Trinh, Cuc Kim; Lee, Hong-Joon; Choi, Jin woo; Kim, Heejoo; Lee, Kwanghee; Lee, Jae-Suk
Abstract : The effect of hydrogen bonding and π–π intermolecular stacking on the physical properties and device performance. Abstract : ( E )-6, 6′-Dibromo-1, 1-bis(2-octyldodecyl)-(3, 3′-biindolinylid-ene)-2, 2′-dione and/or 2, 5-bis(2-octyldodecyl)-3, 6-di(5-bromothien-2-yl)pyrrolo[3, 4- c ]pyrrole-1, 4-(2 H, 5 H )-dione and their t Boc-counterparts were propagated with 2, 5-bis(tributylstannyl)thiophene in a molar ratio of 0.8 : 0.2 : 1.0 to releaseP(ODIDT-BID), P(ODIDT·BDPP), P(ODDPPT·BID) andP(ODDPPT·BDPP) as a new series of random conjugated polymers (RCPs) bearing a large number of octyldodecyl chains to ensure solubility and a small number of thermocleavable t Boc function to cast H-bonding upon heating up to 220 °C. All new polymers were synthesised via Pd catalysed Stille cross-coupling methodology in high yields and reasonable average molecular weights. The cast polymer films exhibited considerable red-shifted UV-vis absorption spectra and a further red-shift was also obtained in the thermal annealed films (at 220 °C for 30 min), which reflected the increasing of crystalline structure. The formation of H-bonding in these polymers was investigated using X-ray diffractometry (XRD) measurements. The field-effect mobilities of these polymers were investigated in the configuration of bottom-gate and bottom-contact (BGBC) field-effect transistors (FETs). The results from FETs indicated that the crystalline structure of RCPs exhibited reasonable FET mobilities with 1.17 × 10 −3 cm 2 V −1 s −1 forP(ODDPPT·BID) and 1.41 × 10 −3 cm 2 V −1 s −1 forP(ODDPPT·BDPP) .